Disease Characteristics of the Singapore Systemic Sclerosis Cohort - Andrea Low Hsiu Ling MRCP, MCI; Teng Gim Gee MBBS, MCI; Law Weng Giap MBBS(Hons), MRCP; Ng Swee Cheng MBBS, MRCP; Amelia Santosa MBBS, MRCP; Grace Chan MD, MRCP; Anita Lim MBChB, MRCP; Png May Ee BEng; Teo Huan Qing Bsc; Lee Ping Ting Bsc(Hons); Julian Thumboo FRCP (Edin), FAMS (Rheumatology) (Proceedings of Singapore Healthcare, 2013)
Introduction: Systemic sclerosis (SSc) has one of the worst prognoses among autoimmune diseases. Multi-ethnic Western cohorts have shown ethnic differences in disease characteristics. Due to a paucity of data in Asia, we aimed to describe the disease characteristics and autoantibody profile of Asian SSc patients. Methods: The Singapore SSc database consists of prevalent and incident cases from four institutions. Data were recorded annually according to a standardised protocol. Cumulative disease characteristics were analysed using descriptive statistics. Results: From 2008 to 2012, 200 patients (85.5% females; Chinese 78%, Malays 10.5%, Indians 6%) diagnosed at a mean age of 46 years, fulfilled the American College of Rheumatology (ACR) (88.0%) or the Very Early Diagnosis of SSc (VEDOSS) (12%) criteria. SSc subtypes include limited cutaneous SSc (LcSSc) (32%) or diffuse cutaneous SSc (DcSSc) (37.6%), SSc-overlap syndromes (27.4%) and sine scleroderma (3%). Predominant disease manifestations were Raynaud's phenomenon (n=161, 80.5%), gastrointestinal (GI) (n=125, 62.5%), joint pain (n=116, 58%) and interstitial lung disease (ILD) (n=99, 51.8%). Pulmonary arterial hypertension (PAH) by echocardiography was present in 23.2% (39/168) of patients (mean systolic pulmonary arterial pressure 55.0+19.7mmHg). Renal crisis was rare (n=4, 2%). Anti-nuclear antibodies (ANA) tested positive in 78.7% (155/197), with anti-Scl-70 (69/197, 35.0%), anti-ribonucleoprotein (RNP) (56/192, 29.2%) and anti-Ro60 (40/193, 20.7%) most frequently detected. Anti-centromere antibodies were infrequent (23/190, 12.1%). Treatment included corticosteroids (80.7%), for peripheral vasculopathy (61.4%), GI (68%), PAH (11.2%) and immunosuppression (62.9%). Conclusion: Compared to Caucasian patients, our predominantly Chinese Asian SSc patients were diagnosed at an earlier age, with more severe PAH, less frequent Raynaud's phenomenon, an autoantibody profile characterised by anti-Scl70, anti-RNP and anti-Ro60, infrequently anti-centromere and more patients had DcSSc.